Community Empowerment Through Computer Course Program for Package C Students at SKB City of Ambon (Peneliti.net, 2023)
Several models of management of non-formal education as stated in the elucidation of the National Education System Law No. 20 of 2003, including study groups, course institutions, training institutions and community learning activity centers or Learning Activity Studios (SKB) is an educational institution that was born from the idea of ​​awareness of the importance of the position of the community in the non-formal education development process. Therefore, the SKB in the midst of the community is expected to be the backbone for the development process to take place by empowering the potentials that exist in the community. The increasing need for non-formal education services in the midst of society, the SKB is currently being developed by various parties, both the community, social, religious, and government institutions (organizations). However, the problems that exist in the field continue to occur. Based on the results of observations and interviews with the leaders of the Ambon City SKB, information was obtained that the Ambon City SKB had conducted computer courses for package C participants for three months, starting from March to May 2023. The purpose of this study was to find out about the implementation of the course program. and how the results were obtained. This is quite interesting to study with the out-of-school education (PLS) concept approach. From the answers of the respondents based on the survey results, it can be seen that more than half (57.14%) of the respondents answered always, a small portion (14.29%) of the respondents answered often, less than half (28.57%) of the respondents answered rarely, and never. none (0%) of respondents answered never. Based on the results of these observations it can be concluded that students always benefit from computer courses.